1998
DOI: 10.1302/0301-620x.80b3.0800508
|View full text |Cite
|
Sign up to set email alerts
|

First metacarpal osteotomy for trapeziometacarpal osteoarthritis

Abstract: We report a long-term follow-up of abduction-extension osteotomy of the first metacarpal, performed for painful trapeziometacarpal osteoarthritis. Of a consecutive series of 50 operations, 41 thumbs (82%) were reviewed at a mean follow-up of 6.8 years. Good or excellent pain relief was achieved in 80%, and 93% considered that surgery had improved hand function, while 82% had normal grip and pinch strength, with restoration of thumb abduction. Trapeziometacarpal osteoarthritis is associated with degeneration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 33 publications
(48 reference statements)
2
36
1
4
Order By: Relevance
“…Furthermore, in a retrospective review of 50 consecutive patients at mean follow-up of 6.8 years, 80 % of patients had goodexcellent pain relief, and 82 % of patients had normal grip and pinch strength. As expected, patients with stage I or II disease had improved outcomes compared with patients with stage III or IV disease [18].…”
Section: Metacarpal Extension Osteotomysupporting
confidence: 76%
“…Furthermore, in a retrospective review of 50 consecutive patients at mean follow-up of 6.8 years, 80 % of patients had goodexcellent pain relief, and 82 % of patients had normal grip and pinch strength. As expected, patients with stage I or II disease had improved outcomes compared with patients with stage III or IV disease [18].…”
Section: Metacarpal Extension Osteotomysupporting
confidence: 76%
“…This then causes cartilage erosion and the symptoms and signs of osteoarthritis (Bettinger et al, 2001). It has been shown that articular degeneration occurs on the palmar side first and gradually progresses to dorsoradial cartilage degeneration in the later stages of osteoarthritis of the joint (Pellegrini, 2005;Hobby et al, 1998). Radiological studies looking at the angle of the trapezium compared to the second metacarpal have shown that there is an increased radial trapezial tilt in Eaton stages III and IV compared to Eaton stages I and II osteoarthritis of the base of the thumb (Bettinger et al, 2001;Kapandji AI and Heim, 2002).…”
Section: Pathophysiology Of Osteoarthritis Of the Base Of The Thumbmentioning
confidence: 99%
“…This ensures that the metacarpal base is covered by the trapezium and joint stability is increased, reducing metacarpal subluxation and wear of the joint cartilage (Zancolli and Cozzi, 1992). Depending on the severity of the symptoms the splint may be effective if just worn nocturnally (Goubau et al, 2007;Hobby et al, 1998). For temporary relief of symptoms, lignocaine and steroid injections into the joint are effective.…”
Section: Treatment Of Trapeziometacarpal Osteoarthritismentioning
confidence: 99%
See 2 more Smart Citations